IMPLEMENTASI PERMENKUMHAM NO.32 TAHUN 2018 TENTANG PERLAKUAN NARAPIDANA LANJUT USIA DI LAPAS KELAS IIB PARIAMAN - Bayu Irito; Herry Fernandes Butar Butar (LPPM Universitas Ekasakti Padang, 2021)
In Indonesia, which is a country that upholds Human Rights (HAM), prisons generally consist of general and elderly inmates, therefore the existence of prisoners who can be said to be elderly has a meaning which is someone who has passed the age of 60 years, so the government make a breakthrough for how elderly prisoners are treated because elderly prisoners are people whose rights of independence are revoked by the court and the inmates can be said to have physical, mental, and social conditions that have started to decline or are no longer healthy can be said to be susceptible to disease , so that the government issued Permenkumham No. 32 of 2018 concerning the Treatment of Elderly Prisoners with the existence of this regulation, it is hoped that the implementation or application of all prisons in Indonesia can be carried out properly where the treatment of elderly inmates consists of: providing assistance to get access to justice; recovery and development of social functions; maintenance and improvement of the health status of elderly prisoners who have begun to decline; and protection of security and safety.